The PEX1 ATPase Stabilizes PEX6 and Plays Essential Roles in Peroxisome Biology - Rinaldi, Mauro A. (Plant Physiol, 2017)
A variety of metabolic pathways are sequestered in peroxisomes, conserved organelles that are essential for human and plant survival. Peroxin (PEX) proteins generate and maintain peroxisomes. The PEX1 ATPase facilitates recycling of the peroxisome matrix protein receptor PEX5 and is the most commonly affected peroxin in human peroxisome biogenesis disorders. Here, we describe the isolation and characterization of, to our knowledge, the first Arabidopsis (Arabidopsis thaliana) pex1 missense alleles: pex1-2 and pex1-3. pex1-2 displayed peroxisome-related defects accompanied by reduced PEX1 and PEX6 levels. These pex1-2 defects were exacerbated by growth at high temperature and ameliorated by growth at low temperature or by PEX6 overexpression, suggesting that PEX1 enhances PEX6 stability and vice versa. pex1-3 conferred embryo lethality when homozygous, confirming that PEX1, like several other Arabidopsis peroxins, is essential for embryogenesis. pex1-3 displayed symptoms of peroxisome dysfunction when heterozygous; this semidominance is consistent with PEX1 forming a heterooligomer with PEX6 that is poisoned by pex1-3 subunits. Blocking autophagy partially rescued PEX1/pex1-3 defects, including the restoration of normal peroxisome size, suggesting that increasing peroxisome abundance can compensate for the deficiencies caused by pex1-3 and that the enlarged peroxisomes visible in PEX1/pex1-3 may represent autophagy intermediates. Overexpressing PEX1 in wild-type plants impaired growth, suggesting that excessive PEX1 can be detrimental. Our genetic, molecular, and physiological data support the heterohexamer model of PEX1-PEX6 function in plants.